2015
DOI: 10.1016/j.foodchem.2015.01.084
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive amines in Mozzarella cheese from milk with varying somatic cell counts

Abstract: The influence of somatic cells counts (SCC) in milk on bioactive amines in Mozzarella cheese was investigated. High SCC milk had lower lactose and higher pH compared to low and medium SCC. Low spermine levels were found in milk irrespective of SCC. The cheeses had similar characteristics, but the extension and depth of proteolysis increased with SCC. Cheese from all SCC categories contained spermine; whereas tyramine and tryptamine were only detected in cheese from high SCC milk. During 60-days refrigerated st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
1
7
0
2
Order By: Relevance
“…Cheese bread with cowpea (F) (average ± SD) Total Phenolics (mg GAE/100g) 105.3 ± 5.16ª 188.4 ± 8.92 b Total Flavonoids (mg EQ/100g) 51.7 ± 1.6ª 85.9 ± 2.77 b Condensed Tannins (mg EC/100g) 3.5 ± 0.0 a 7.0 ± 0.28 b SD -Standard Deviation; GAE -Equivalent to gallic acid; EQ -Equivalent to quercetine; EC -Equivalent to catechin; The use of the same letters between the standard cheese bread and cheese bread with cowpea indicates that there is no significant difference between the means, based on the Student's t test at the level of 5%, 95% confidence interval. and Ubaldo et al (2015), cheese contains significant levels of histamine, putrescine, cadaverine, and spermidine. The main factors affecting the formation and accumulation of biogenic amines in cheese are the availability of amino acids, the presence of microorganisms with the appropriate catabolic pathway activated and environmental conditions favorable to the decarboxylation activity.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Cheese bread with cowpea (F) (average ± SD) Total Phenolics (mg GAE/100g) 105.3 ± 5.16ª 188.4 ± 8.92 b Total Flavonoids (mg EQ/100g) 51.7 ± 1.6ª 85.9 ± 2.77 b Condensed Tannins (mg EC/100g) 3.5 ± 0.0 a 7.0 ± 0.28 b SD -Standard Deviation; GAE -Equivalent to gallic acid; EQ -Equivalent to quercetine; EC -Equivalent to catechin; The use of the same letters between the standard cheese bread and cheese bread with cowpea indicates that there is no significant difference between the means, based on the Student's t test at the level of 5%, 95% confidence interval. and Ubaldo et al (2015), cheese contains significant levels of histamine, putrescine, cadaverine, and spermidine. The main factors affecting the formation and accumulation of biogenic amines in cheese are the availability of amino acids, the presence of microorganisms with the appropriate catabolic pathway activated and environmental conditions favorable to the decarboxylation activity.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…In fact, some studies on raw milk Manchego cheese corroborate the presence of BAs in high quantities [ 8 , 9 ]. On the other hand, it is well known that mastitis can affect quality and enhance proteolysis in milk, and some authors have found a relationship between the somatic cell counts in milk and the content of biogenic amines in cheeses made with that milk [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…SCC results in decreased cheese yield as a consequence of the low casein content, which results in products of low quality and stability (COONEY et al, 2000). Cheeses made from milk with different levels of SCC had similar characteristics, but the extension and depth of proteolysis increased with SCC (UBALDO et al, 2015). High SCC milk induces an accelerated breakdown of αS1-casein.…”
mentioning
confidence: 99%